(untitled) (Journal of Nepal Geological Society, 1996)
Before independence only a few mineral commodities were mined in Pakistan. But at present, the Geological Survey of Pakistan has identified favourable areas of mineralization of aluminium, chromium, copper, lead, zinc, gold, silver, iron, platinum and tungsten. Similarly, very large deposits of industrial minerals such as gypsum, anhydride, limestone, dolomite, building stones, rock salt, silica sand, barite, fuller’s earth, industrial clays and soap stone and medium sized resources of magnesite, china clay, and bentonite occur in the country. Recent discovery of over 175 billion tonnes of good quality lignite in the Thar coal field has put Pakistan into 11th position in the world among the countries with large coal deposits. After exploitation of these resources Pakistan would be an important mineral producer in near future. This paper briefly presents the overview of mineral resources of Pakistan and also describes the status of metallic and non-metallic minerals.